Desconstrução dos estereótipos e arquétipos femininos no filme Garota Exemplar - OLIVEIRA, Isabela Sanches de (2024)
Femininity, throughout history, was built around extremely patriarchal and sexist societies which led women to be socially subjected to pre-determined roles and positions, which focused mainly on issues of aesthetic idealization and positions of subservience to men within their marriages. Despite such dynamics, currently, demands and discussions around such topic at the most diverse contexts converge around the importance of struggling against such archetypes and stereotypes. Given this scenario, the movie Exemplary Girl, released in 2014, proves to be a very interesting work to discuss the breaking of such patterns, since, in addition to presenting a protagonist which diverges psychologically and completely from such positions. The movie still does it in na intelligent way, by using the patterns around its protagonist, at na early stage, as a necessary narrative resource for the construction of its dramatic plot to surprise the viewer with the unfolding of the story told. Therefore, this work’s main objective is to promote a discussion around the archetypes and stereotypes of femininity deconstruction based on na analysis of the movie Exemplary Girl and its protagonist. In relation to specific objectives, the aim is to promote na overall analysis of the work, taking into account the perspectives it offers at its narrative; to describe the patterns of femininity that, initially, the movie builds up around its protagonist; and to present the work’s plot twist as the narrative resource which leads to the breaking point of the patterns previously presented, thus being a turning point not only to the plot itself, but in how the image of the protagonist has been constructed to the viewer until then . To develop the research, bibliographical research (Gil, 2008) was used from a qualitative perspective (Cardano, 2017). Regarding its structure, this work has three chapters: Theoretical foundation, where the selected authors and the methodology adopted are discussed; in Contextualizing the movie Exemplary Girl, the audiovisual work analyzed is presented, at its generality, as well as in its plot; Finally, the chapter The deconstruction of Exemplary Girl feminine archetypes and stereotypes presents a discussion on how Exemplary Girl promotes the deconstruction of archetypes and stereotypes of femininity as a narrative resource that contributes to the construction of its psychological dramatic plot.